MYSTICAL DISCOURSE IN JAVA IN THE 18TH CENTURY NARRATED BY THE BOOK OF CABOLEK - Hamid Nasuhi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
This article discusses the discourse of Sufism in the 18th century in Java as narrated by Serat Cabolek by Kiai Yasadipura I (1729-1803). This manuscript tells about the trial of Kiai Ahmad Mutamakin in front of the authorities of the Mataram Kingdom in Kartasura. This cleric from the village of Cabolek, Tuban, in the northern coast of Java was controversial and accused of spreading Ilmu Hak, namely wujudiyah Sufism, to commoners, even though his knowledge capacity was considered inadequate by the religious scholars (ulama) who opposed him. In that trial Kiai Mutamakin was found guilty, but later was granted pardon by King Pakubuwana II (1726-1749). The author of Serat Cabolek not only recorded the chronological details of Kiai Mutamakin's trial, more than that he also emphasized his stance on how the Javanese should direct their religious orientation. Yasadipura I, as a court poet with educational background of pesantren (Islamic boarding school), figured Ketib Anom as an ideal Javanese Muslim. This religious head officer from Kudus is a figure that perfectly described not just having in-depth knowledge of traditional Javanese mysticism, namely the mystical story of Dewaruci, but also mastering and carrying out the provisions of the Shari'a in Islam.